ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN TEKNOLOGI INFORMASI PADA AKUNTAN PUBLIK DI SEMARANG - Wulandari, Wuragil Septi; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2013)
This study aimed to determine the effect of social factors, compliance tasks, long-term consequences, affect, complexity, and the conditions that facilitate the use of information technology in public accounting in Semarang. It also aims to provide empirical evidence of a positive relationship between social factors, the suitability of the task, long-term consequences, affect, complexity, and the conditions that facilitate the use of information technology in public accounting in Semarang.This study used population Auditor Public Accounting Firm (KAP) in the area of Semarang. The sample used was 66 respondents. Hypothesis test in this study using multiple linear regression analysis.The results of this study indicate that all the independent variables significantly have a positive effect on the dependent variable. It means that social factors, compliance tasks, long-term consequences, affect, complexity, and facilitating conditions have a positive and significant impact on the utilization of information technology on public accounting in Semarang. Higher levels the social factors, the suitability of the task, long-term consequences, affect, complexity, and the conditions that facilitate the greater use of information technology on public accounting resulting in Semarang.